2015
DOI: 10.1099/vir.0.068312-0
|View full text |Cite
|
Sign up to set email alerts
|

Temporal proteomic analysis and label-free quantification of viral proteins of an invertebrate iridovirus

Abstract: Invertebrate iridescent virus 6 (IIV-6) is a nucleocytoplasmic virus with a~212 kb linear dsDNA genome that encodes 215 putative ORFs. The IIV-6 virion-associated proteins consist of at least 54 virally encoded proteins. One of our previous findings showed that most of these proteins are encoded by genes from the early transcriptional class. This indicated that these structural proteins may not only function in the formation of the virion, but also in the initial stage of viral infection. In the current study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Iridovirid genomes contain multiple genes coding for kinases and phosphatases that perform important post-translational modifications of proteins to help regulate protein activities over the course of the infection [ 127 ]. Active expression of these virus-encoded phosphatases and kinases involved in dephosphorylation and phosphorylation reactions was observed by proteomic analysis of infected cells.…”
Section: Virion Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Iridovirid genomes contain multiple genes coding for kinases and phosphatases that perform important post-translational modifications of proteins to help regulate protein activities over the course of the infection [ 127 ]. Active expression of these virus-encoded phosphatases and kinases involved in dephosphorylation and phosphorylation reactions was observed by proteomic analysis of infected cells.…”
Section: Virion Proteinsmentioning
confidence: 99%
“…However, the roles of several kinases have been elucidated. One putative serine/threonine kinase (380R) was present in high abundances in IIV-6 virions [ 127 ]. A purified serine/threonine protein kinase 389L (also called iridoptin) induced apoptosis in insect cells and was initially thought to be associated with the IIV-6 virion structure [ 137 ].…”
Section: Virion Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the key enzymes in these DNA repair pathways can be found in the genomes of Megavirales (Table S1). Transcriptomic ( [24,[28][29][30][31][32][33]) and proteomic ( [24,[34][35][36][37]) studies revealed that many of these DNA repair genes are transcriptionally active during infection and that gene products (i.e., enzymes) are packaged into Megavirales virions (Table S1). Individual Megavirales genomes encode 0 up to 15 of those genes (3.6 genes on average).…”
Section: Why Do Megavirales Genomes Encode Many Dna Repair Genes?mentioning
confidence: 99%